Optimization the process of chemically modified carbon nanofiber coated monolith via response surface methodology for CO2 capture - Malekbala, Mohamad Rasool; Soltani, Soroush; Abdul Rashid, Suraya; Abdullah, Luqman Chuah; Rashid, Umer; Nehdi, Imededdine Arbi; Choong, Thomas Shean Yaw; Teo, Siow Hwa (MDPI, 2020)
In the present study, a sequence of experiments was performed to assess the influence of the key process parameters on the formation of a carbon nanofiber-coated monolith (CNFCM), using a four-level factorial design in response surface methodology (RSM). The effect of reaction temperature, hydrocarbon flow rate, catalyst and catalyst promoter were examined using RSM to enhance the formation yield of CNFs on a monolith substrate. To calculate carbon yield, a quadratic polynomial model was modified through multiple regression analysis and the best possible reaction conditions were found as follows: a reaction temperature of 800 °C, furfuryl alcohol flow of 0.08525 mL/min, ferrocene catalyst concentration of 2.21 g. According to the characterization study, the synthesized CNFs showed a high graphitization which were uniformly distributed on a monolith substrate. Besides this, the feasibility of carbon dioxide (CO2) adsorption from the gaseous mixture (N2/CO2) under a range of experimental conditions was investigated at monolithic column. To get the most out of the CO2 capture, an as-prepared sample was post-modified using ammonia. Furthermore, a deactivation model (DM) was introduced for the purpose of studying the breakthrough curves. The CO2 adsorption onto CNFCM was experimentally examined under following operating conditions: a temperature of 30–50 °C, pressure of 1–2 bar, flow rate of 50–90 mL/min, and CO2 feed amount of 10–40 vol.%. A lower adsorption capacity and shorter breakthrough time were detected by escalating the temperature. On the other hand, the capacity for CO2 adsorption increased by raising the CO2 feed amount, feed flow rate, and operating pressure. The comparative evaluation of CO2 uptake over unmodified and modified CNFCM adsorbents confirmed that the introduced modification procedure caused a substantial improvement in CO2 adsorption.